PENINGKATAN KEMAMPUAN MENYUSUN KALIMAT MAJEMUK DENGAN KONJUNGSI MELALUI METODE DRILL PADA SISWA KELAS VII B SMP NEGERI 12 DENPASAR TAHUN PELAJARAN 2014/2015 - I Gusti Ayu Ririn Juliana; I G.A.P. Tuti Indrawati; Ni Luh Sukanadi (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
This study aims to determine the success of the Drill method in an effort to improve the ability of VII B grade students in composing compound sentences with conjunctions in Denpasar Public Middle School 12. The scope of this research is the application of the Drill method to improve the ability to compile compound sentences with conjunctions in class VII B of SMP Negeri 12 Denpasar in the academic year of 2014-1015. The type of method used in this study is Drill (exercise), this method emphasizes repetitive aspects of training, thus providing permanent skills to students.Conclusions in the pre cycle showed that the ability of students not yet fulfilling the minimum completeness criteria was 75, with the average value obtained was 4.35 with less categories. Then the data acquisition was continued on the cycle I action which had experienced a slight increase but had not met the criteria of 5.5 with almost enough categories. With the acquisition of data in the first cycle which states that it has not fulfilled the KKM so that it continues on the second cycle, in the second cycle the average score obtained by students is 66.5 with sufficient categories, in the third cycle the average student can fulfill the KKM is amounting to 8.17 in the good category. The results obtained from cycle I, cycle II, and cycle III have increased and have met the Mininum Mastery Criteria (KKM) that apply in the school that is equal to 75, this proves that the Drill method used can improve students' abilities in composing compound sentences.